Simulation optimisation of displaced left-turn intersection layout with multi-objectives. (5th April 2023) - Shao, Qianqian; Zheng, Yingcheng; Liu, Yang; Xing, Yan
Displaced left-turn (DLT) intersections, which effectively solve the conflict between left-turn and opposing-through traffic, are currently the most efficient innovative intersection design. However, the special layout of DLT will inevitably cause high difficulty in channelisation design. For full use of the potential traffic capacity of DLT intersection, a multi-objective optimisation model for intersection with DLT layout (MOOM-DLTL) is built based on integrated simulation and mathematical programming (ISMP) framework. In this model, the signal scheme is regarded as the accompanying strategy of DLT layout optimisation to describe the interaction between layout and signal control. In addition, the multi-objective particle swarm optimisation based on shift-based density estimation (MOPSO+SDE) algorithm is developed to obtain the Pareto front of the proposed model. A series of experimental results show that the proposed optimisation method is successful in improving the traffic efficiency of DLT intersection.